From Colors to Spectra and Back Again: First Near-IR Spectroscopic Survey of Neptunian Trojans - Larissa Markwardt; Hsing Wen Lin; Bryan J. Holler; David W. Gerdes; Fred C. Adams; Renu Malhotra; Kevin J. Napier (The Planetary Science Journal)
In this work, we present 0.7–5.0 μ m spectra of eight Neptunian Trojans (NTs) as observed by the JWST’s NIRSpec instrument. The reddest NT, 2013 VX _30 , exhibits a unique spectrum with strong absorption features between 3 and 4 μ m, while the bluest NT, 2006 RJ _103 , shows negligible water absorption. A principal component analysis comparing these spectra with those of trans-Neptunian objects (TNOs) and Centaurs reveals that most NTs belong to the “bowl-type” spectral group, while 2013 VX _30 is categorized as “cliff-type” in the N. Pinilla-Alonso et al. taxonomy. For the bluest NT in our sample, 2006 RJ _103 shows some evidence that it may be related to carbonaceous asteroids. For the red object 2011 SO _277 , we find no close TNO spectral counterpart. Except for the true outlier 2011 SO _277 , NTs have better spectral analogs among Plutinos and distant Centaurs, suggesting that spectral variation within major groups may arise from current temperature and location, rather than solely from formation regions. Finally, we highlight optical slope (S′) and near-IR slope (SIR _1 ) as effective indicators for distinguishing spectral groups and identifying outliers. These findings enable the use of broadband photometry to explore NT and TNO surface compositions, especially for faint objects, which will be directly applicable to large photometric surveys like the Dark Energy Survey and the Vera C. Rubin Observatory’s LSST.